2016
DOI: 10.1038/srep30803
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Optical Activity in High Index Dielectric Nanoantennas

Abstract: The magneto-optical activity, namely the polarization conversion capabilities of high-index, non-absorbing, core-shell dielectric nanospheres is theoretically analyzed. We show that, in analogy with their plasmonic counterparts, the polarization conversion in resonant dielectric particles is linked to the amount of electromagnetic field probing the magneto-optical material in the system. However, in strong contrast with plasmon nanoparticles, due to the peculiar distribution of the internal fields in resonant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 58 publications
1
45
0
Order By: Relevance
“…Indeed, the magneto-optical control of the resonant behavior in plasmonic systems, and the complementary enhancement of the magneto-optical response due to the same resonances, is behind the success of the field of magnetoplasmonics [13]. In the last few years, the standard magnetoplasmonic system exhibiting electric resonances has been extended to consider other situations, such us the exploitation of magnetic resonances [14][15][16], or even the control of thermal radiation and radiative heat transfer at room temperature [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the magneto-optical control of the resonant behavior in plasmonic systems, and the complementary enhancement of the magneto-optical response due to the same resonances, is behind the success of the field of magnetoplasmonics [13]. In the last few years, the standard magnetoplasmonic system exhibiting electric resonances has been extended to consider other situations, such us the exploitation of magnetic resonances [14][15][16], or even the control of thermal radiation and radiative heat transfer at room temperature [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In order to quantify these near-field results in a more comprehensive way, and reveal the exact spectral positions of the plasmonic resonances, we calculate the induced dipole moment in the AuNP. In the small particle limit, the dipole moment induced in the AuNP, which is embedded in the dielectric Bi: YIG, is given by the following formula: 40,41…”
Section: Near-field Simulations and Analysismentioning
confidence: 99%
“…This resonance is the result of polarization coupling, and it is mediated through the magneto-optical properties of Bi:YIG, giving rise to the broadband enhancement of the polarization conversion. 40,41 Indeed, if we express the complex oscillating electric dipole in the AuNP as p = α Au E i , where E i stands for the electric field of the incident light, then it can be shown that in linear response of ϵ yz :…”
Section: Far-field Simulations and Analysismentioning
confidence: 99%
“…[13] Such periodic phase gradients have been employed for the efficient coupling of light into surface modes [14] and for the development of metalenses. [17,18] Silicon-based metamaterials have been the base to create phase gradients by changing the geometry and distribution of the nanostructures on the surface. [17,18] Silicon-based metamaterials have been the base to create phase gradients by changing the geometry and distribution of the nanostructures on the surface.…”
Section: Doi: 101002/adom201600933mentioning
confidence: 99%